Адсорбция органических веществ из воды - Когановский А. М. Александр Маркович; Клименко Н. А. Наталья Аркадьевна; Левченко Т. М. Тамара Моисеевна; Рода И. Г. Игорь Григорьевич (Ленинград, Химия, 1990)
Авт. указаны на обороте тит. л.